(untitled) (Neo Science Peer Reviewed Journal, 2022)
The article describes the content of teaching technology lessons in general secondary education based on didactic principles. It discusses ways to develop students mentally and physically, how to work with them, how to focus on reading and learning, and how to organize students’ personal activities